Development of Integrated Economic Learning Materials Entrepreneurship Values for High School - Dhewi Suryani; Endang Mulyani (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This research objective is to develop integrated economic teaching in entrepreneurial values and find out eligibility for high school X-IPS1 students. They were using research and development (R&D) methods. The stages of the research include the initial research and information collecting, planning, develop preliminary form a product, preliminary field testing, leading product, operational product revision, and final product revision. The research Subjects used in this study include two validators, namely learning media experts, 37 class X-IPS1 students, and one economics teacher. The result achieved in the development of integrated economic teaching materials are entrepreneurial values, namely creative value, independence values, leadership values, risk-bearing values, and action-oriented values that were developed were categorized as useful from the aspects of content worthiness, language presentation was more than 75%. So the result of these studies can be entrepreneurial values are appropriate for use in learning in High School Class.